R RANCANG BANGUN MEDIA PEMBELAJARAN DIGITAL BERBASIS AUGMENTED REALITY CARD PADA MATERI METAMORFOSIS HEWAN DI KELAS IV SD - Gumilang Pawitan; Yunus Abidin; Rendi Restiana Sukardi (Universitas PGRI Adi Buana Surabaya, 2023)
This research is a type 1 design and development (D&D) research concerning product development with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The purpose of this research is to find out how to design a digital learning media based on augmented reality cards on animal metamorphosis material in class IV SD and to find out the user's response to digital learning media based on augmented reality cards on animal metamorphosis material in class IV SD. This research involved material experts, media experts, and teacher and student responses. The instruments used in this study were questionnaires and interviews. Research begins with the process of analyzing learning materials, users, and device needs, then designing media starting from making Media Program Outlines (GBPM), flowcharts, making 2-dimensional visuals, making 3-dimensional visuals, and application interfaces. The product uses material expert assessment with a level of reliability using Cornbach's Alpha and validation results using Aiken's V. Furthermore, the product also uses assessment from media experts with a level of reliability using Cohen's Kappa and validation results using Aiken's V. The overall response from users gets very positive results for the media digital learning based on augmented reality cards. The final accumulation result of the response data is very appropriate. Based on the results of teacher and student responses, it was stated that learning media based on augmented reality cards were very suitable for use in the science learning process for animal metamorphosis material and could be used on an ongoing basis by users.